RANAH RUMAH TANGGA BENTENG TERAKHIR PEMERTAHANAN BAHASA MOSSO DI KAMPUNG MOSSO KOTA JAYAPURA (Household Domain is the Last Effort to Survive Mosso Language of Mosso Vilage in Jayapura) - Arman Arman (SAWERIGADING, 2014)
The purpose of this paper is to know language situation of Mosso language in household domain and language choice by the Mosso speakers in the domain. The research uses quantitative method and applies sociolinguistic approach. Result of research shows that elder people are still active using Mosso language in household domain. It is shown by its effect to the younger. Even though the youngers are able to speak Indonesian language, they are fluent and prefer to speak in Mosso language. In addition, based on anava, the research shows the influence of age in relation to language chosen by the speaker, yet, it is not really significant.